The Lifestyle Patterns of the Rumahtiga Community Regarding Environmental Cleanliness of Rumahtiga Beach in Rumahtiga Village, Teluk Ambon Subdistrict - Ngosiem, Christofol; Manakane, Susan Evelin; Leuwol, Ferdinand Salomo (Universitas Pattimura, 2024)
This study aims to describe the lifestyle patterns of the community related to beach cleanliness in Negeri Rumahtiga, Ambon City. The research method used is descriptive qualitative with data collection techniques through observation, interviews, questionnaires, and documentation. The study population includes all residents of Negeri Rumahtiga, with a sample of 20 individuals selected using purposive sampling techniques. The results show that community awareness of beach cleanliness is quite high, with the majority of respondents strongly agreeing (50%) and agreeing (50%) on the need to maintain cleanliness. The beach cleanliness initiative programs involving active community participation, support from local government, and educational campaigns on reducing single-use plastic have shown positive yet not optimal results. This study recommends enhancing waste management infrastructure, continuous education, and strengthening environmental care communities as strategic steps in maintaining beach cleanliness